Interactive Daily Spin Board: Revolutionizing Language Learning for Young Children - Priani, Ni Kadek Dian; Kristiantari, Maria Goreti Rini (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Children often encounter challenges in learning new materials, necessitating the development of educational media that stimulates their growth. This study aims to develop an interactive PowerPoint-based daily spin board to enhance language skills in Group B children. The research employed the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The product was evaluated by one content expert, one instructional design expert, and one instructional media expert. The study subjects included three children in individual trials, nine children in small group trials, and 16 children for effectiveness testing. Data were collected through questionnaires and observation and analyzed using quantitative descriptive and inferential statistical methods. The expert evaluations yielded excellent results, with scores of 100% for product design, 98.33% for content, 90.63% for instructional design, and 92.18% for instructional media. Individual and small group trials received scores of 93.33% and 93.89%, respectively, classified as excellent. Effectiveness testing indicated a significant impact, with tstatistics > ttable (9.079 > 1.753). The findings confirm that the interactive PowerPoint-based daily spin board is both feasible and effective for improving language skills in Group B children. This study implies that the daily spin board facilitates language learning by providing an engaging alternative to traditional book-based approaches, reducing monotony and increasing children’s learning engagement.